Ultrasonic-Assisted Extraction of Polysaccharides from Brassica rapa L. and Its Effects on Gut Microbiota in Humanized Mice - Mengying Zhang; Wei Wang; Wei Li; Zhipeng Wang; Kaiyue Bi; Yanbo Li; Yuhan Wu; Yu Zhao; Rui Yang; Qingping Du (Foods)
This study optimized ultrasound-assisted extraction (UAE) for polysaccharide isolation from Brassica rapa L. using Box–Behnken design, achieving a maximum yield of 41.12% under conditions of 60 °C, 60 min, 175 W ultrasonic power, and 30 mL/g liquid–solid ratios. The crude polysaccharide (BRAP) was purified via DEAE-52 cellulose and Sephadex G-100 chromatography, yielding BRAP1-1 with the highest recovery rate. Structural analyses (FT-IR, HPGPC, SEM, SEC-MALLS-RI) identified BRAP1-1 as a β-glycosidic pyranose polysaccharide (32.55 kDa) composed of fucose, rhamnose, arabinose, galactose, and galacturonic acid (molar ratio 0.81:4.30:3.61:1.69:89.59). In a humanized mouse model via fecal microbiota transplantation (FMT), BRAP1-1 significantly increased α-diversity indices (ACE, Chao1; p < 0.05) and altered β-diversity, with PCA explaining 73% variance (PC1: 60.70%, PC2: 13.53%). BRAP1-1 elevated beneficial genera (Lysinibacillus, Solibacillus, Bacteroides, etc.) while suppressing pathogens (Treponema, Flavobacterium, etc.). Six genera, including [Eubacterium]_coprostanoligenes_group and Bacteroidales (p < 0.05), correlated with acetic/propionic acid production. These findings demonstrate BRAP1-1’s potential to modulate gut microbiota composition and enhance intestinal homeostasis.